Development of Micro, Small and Medium Enterprises (MSMEs) Based on Creative Industry in Ulunoyo District, South Nias Regency - Ndruru, Hubertus Harisman; Zebua, Dedi Irawan; Bate'e, Maria Magdalena; Gulo, Heniwati (PT. Maju Malaqbi Makkarana, 2025)
This study examines the development of creative industry-based Micro, Small, and Medium Enterprises (MSMEs) in Ulunoyo District, South Nias Regency, with a focus on four main sectors: culinary, crafts, fashion, and music. The purpose of this study is to describe the condition of creative MSMEs in Ulunoyo, identify the obstacles faced, and analyze the development strategies implemented by business actors to increase competitiveness. The method used is descriptive qualitative with data collection techniques through interviews, field observations, and documentation of 21 MSME actors in five villages. Data analysis was carried out through reduction, presentation, and verification of findings. The results show that the development of creative MSMEs in Ulunoyo is supported by the potential of community creativity, strategic location, and the existence of traditional markets as distribution centers. Development strategies include improving product quality, business diversification, design innovation, and the use of digital technology for promotion and marketing. However, a number of major obstacles are still encountered, including limited business capital, rising raw material prices, low managerial skills, lack of product innovation, limited market access, and high levels of competition. To overcome these obstacles, business actors carry out creative promotions, expand their collaboration networks, and utilize social media to reach a wider consumer base.